Security Management Analysis of Security Services Using Framework COBIT 5 Domain DSS05 - Wahyudi, Agus Anwar Eka; Ayu, Dewa; Aryani, Ni Wayan Sri (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
Immigration Denpasar Office is one of the technical service units performing task and function Directorate General of Immigration. The immigration document publishing is one of the functions of the services implemented by Immigration Office Denpasar. Data security is the most important thing in document publishing activities for Indonesian. To find out the level of capability and conditions of IT governance in document publishing service for Indonesians, an IT governance analysis activity relates to service management in security and data accuracy is required. The results of the analysis are expected to produce recommendations to improve IT management related to security services, it can better support the organization’s bussiness objectives in the future. The study used capability model as a measuring tool to respondents answers related to questionnaires based on COBIT 5 domain DSS05 (Manage Security Service) framework consisting of 8 subprocesses, with total 43 statements. The result of the recapitulation show the level 3 with the status of Largely Achieved gained 83% indicates the process of information security services have done regulary implemented.